2015
DOI: 10.1097/ico.0000000000000335
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Ocular Manifestations of Pemphigus and Bullous Pemphigoid Identifies a High Prevalence of Dry Eye Syndrome

Abstract: The high occurrence of patient-reported ocular symptoms and clinical evidence of dry eye on Schirmer testing and break-up time demonstrate high prevalence of DES in our cohort of pemphigus and BP patients, which is a novel finding. Limbal broadening was another common finding not previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…A deepened understanding of the impact of intercellular cohesion among meibocytes during differentiation and the associated processes is of relevance because an increasing number of case reports also described eye involvement in patients with PV. 39e41 In a broad case study from 2015, Tan et al 7 further identified a high prevalence of DED in patients with PV. Here as well as in the recent in situ study, 5 we demonstrated that meibocytes display a composition of adhesion molecules similar to the epidermis, including Dsg1 and Dsg3 as the primary targets of PV autoantibodies.…”
Section: The Role Of Mgd For Ocular Involvement In Pemphigusmentioning
confidence: 99%
See 1 more Smart Citation
“…A deepened understanding of the impact of intercellular cohesion among meibocytes during differentiation and the associated processes is of relevance because an increasing number of case reports also described eye involvement in patients with PV. 39e41 In a broad case study from 2015, Tan et al 7 further identified a high prevalence of DED in patients with PV. Here as well as in the recent in situ study, 5 we demonstrated that meibocytes display a composition of adhesion molecules similar to the epidermis, including Dsg1 and Dsg3 as the primary targets of PV autoantibodies.…”
Section: The Role Of Mgd For Ocular Involvement In Pemphigusmentioning
confidence: 99%
“…42,43 Therefore, it cannot currently be ruled out that autoantibodies in pemphigus interfere with signaling pathways required for physiologic processes of meibocytes besides cell adhesion and lipid production. Because ocular pemphigus still remains underdiagnosed 7,39 and no eye biopsy specimens of patients with PV are available, the novel ex vivo slice culture model of human eyelids may be a promising model for further studies on the signaling pathways involved in PV pathogenesis. Moreover, the model may provide new insights into the role of intercellular cohesion and its regulation, which ultimately may also allow the establishment and testing of new therapeutic approaches for treatment of MGD-associated diseases.…”
Section: The Role Of Mgd For Ocular Involvement In Pemphigusmentioning
confidence: 99%
“…Most reports of ocular involvement include single cases or case series, and underreporting has been suggested (Palleschi et al , ). Blepharitis and mild conjunctivitis are the most common presentations with signs of dry eye disease in almost all patients (Tan et al , ). Eyelid and conjunctival erosions as well as conjunctival masses have also been reported (Broussard et al , ).…”
Section: Ocular Involvement In Vesiculobullous Disordersmentioning
confidence: 99%
“…Further, severity scores from such tools can be utilised to guide treatment decisions and evaluate outcomes. Both EB/AIBD have been documented to cause severe ocular complications [ 3 , 5 8 ]. Thus, careful ophthalmological assessment, ideally with the aid of a validated scoring system, should be an essential part of the multidisciplinary management of these patients.…”
Section: Introductionmentioning
confidence: 99%